The physical properties of P2O5-Sm2O 3-MnO2 glass system - Sahar, Md Rahim; Astuti, B.; Rohani, M.S. (The Optical Society of Japan, co-published with Springer-Verlag GmbH, 2006)
Phosphate glasses doped with samarium oxide have been made using the melt quenching technique. The density of the glass was determined using the Archimedes method while the Vickers hardness was measured using a micro-vicker tester. Both density and hardness have shown an increasing trend with the addition of a small amount of Sm2O3. The refractive index was characterized using UV-visible spectroscopy and the Sellmeier fitting equation was used to verify the result. The refractive index was found to vary from 1.972 to 1.807 depending on the wavelength and well agreed with the fitting curve.